2013
DOI: 10.4028/www.scientific.net/kem.554-557.1282
|View full text |Cite
|
Sign up to set email alerts
|

Force Prediction for Correction of Robot Tool Path in Single Point Incremental Forming

Abstract: Abstract. In this work, an off-line compensation procedure, based on an elastic modelling of the machine structure coupled with a Finite Element Analysis (FEA) of the process is applied to Robotized Single Point Incremental Forming (RSPIF). Assuming an ideal stiff robot, the FEA evaluates the Tool Center Point (TCP) forces during the forming stage. These forces are then defined as an input data of the elastic robot model to predict and correct the tool path deviations. In order to make efficient the tool path … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…Industrial robots possess a large working volume, fast drives, low stiffness and lower allowable forces [32]. Due to the high flexibility, Robo-forming finds applications for industrial prototypes and batch-type production.…”
Section: Forming Machinery and Forming Forcementioning
confidence: 99%
See 2 more Smart Citations
“…Industrial robots possess a large working volume, fast drives, low stiffness and lower allowable forces [32]. Due to the high flexibility, Robo-forming finds applications for industrial prototypes and batch-type production.…”
Section: Forming Machinery and Forming Forcementioning
confidence: 99%
“…Chera et al [31] investigated the capacity of Kuka industrial robot during the SPIF process in terms of forming forces. The results showed that maximum value of force in the axial direction was close to 230 N and force capacity of the Kuka KR6 robot was approximately 310 N. Jeremy et al [32] and Belchior et al [33] compared the forming forces obtained from industrial robot with those obtained from a three-axis milling machine on AA5086-H111 sheets. Results showed that the forming force obtained from CNC milling machine setup was 30% more than that produced by industrial robot as given in Table 1.…”
Section: Forming Machinery and Forming Forcementioning
confidence: 99%
See 1 more Smart Citation
“…The limitation of lower stiffness and accuracy for robotic structures can be eliminated by parallel robotic structures. Also, the industrial robots proved to be effective in forming a part with the same standard parameters, because require lower values of the forming forces, compared to CNC milling machines [17].…”
Section: Fig 1 Spif Process Principlementioning
confidence: 99%
“…Knowing the values of the maximum forces that can occur during this process help researchers to prevent material degradation and at the same time to choose the suitable equipment that can perform the incremental deformation process on the material used. Furthermore, according to a study done in the paper [6], force prediction helps correcting the trajectories made by the punch so that the final shape and precision of the desired piece will be improved, which is extremely important for the cranial implants.…”
Section: Force and Thickness Prediction With Finite Element Analysismentioning
confidence: 99%